Pengaruh Dukungan Orang Tua terhadap Perencanaan Karir Siswa MAN 1 Padang Panjang - Syahrul Ramadhan; Alfi Rahmi (Lembaga Yasin AlSys, 2026)
Career planning is an important aspect of preparing students for further education and the world of work, but some students at MAN 1 Padang Panjang do not yet have clear career plans, as indicated by their limited efforts to seek career information and suboptimal parental involvement. This study aimed to analyze the effect of parental support on the career planning of students at MAN 1 Padang Panjang. The study employed a quantitative approach with a correlational design. The research population consisted of 323 Grade X students in the 2025/2026 academic year, with a sample of 180 students selected through proportionate stratified random sampling. Data were collected using a parental support questionnaire and a career planning questionnaire that met the criteria for content validity based on Aiken’s V and reliability based on the Intraclass Correlation Coefficient (ICC). The data were analyzed using normality testing, linearity testing, and simple linear regression. The results showed that parental support had a positive and significant effect on students’ career planning, with F = 8.732 and p = 0.004 < 0.05. The regression equation Y = 68.043 + 0.162X indicated that increased parental support was followed by improved career planning. The coefficient of determination, R² = 0.047, indicated that parental support contributed 4.7% to the variation in students’ career planning. These findings confirm that parental support plays a role in the development of career planning, although its contribution is relatively limited. The implications of this study indicate the need for schools and Guidance and Counseling teachers to strengthen collaboration with parents in providing career information, exploration, and planning services for students.